2015
DOI: 10.1017/s0272263115000339
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Cognitive Task Demands Using Dual-Task Methodology, Subjective Self-Ratings, and Expert Judgments

Abstract: This study explored the usefulness of dual-task methodology, selfratings, and expert judgments in assessing task-generated cognitive demands as a way to provide validity evidence for manipulations of task complexity. The participants were 96 students and 61 English as a second language (ESL) teachers. The students, 48 English native speakers and 48 ESL speakers, carried out simple and complex versions of three oral tasks-a picture narrative, a map task, and a decision-making task.Half of the students completed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
88
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 128 publications
(106 citation statements)
references
References 39 publications
16
88
2
Order By: Relevance
“…As in Révész et al. (), we found that speakers’ ratings of the cognitive load increased significantly from the simple task ( M = 5.08, SD = 2.20) to the complex task ( M = 5.87, SD = 1.98), F (1, 38) = 5.56, p = .024, ƞ p 2 = .13. The same was found for writers, whose ratings increased from the simple ( M = 3.64, SD = 1.58) to the complex condition ( M = 5.03, SD = 1.86), F (1, 38) = 19.04, p < .0001, ƞ p 2 = .33.…”
Section: Methodssupporting
confidence: 85%
See 3 more Smart Citations
“…As in Révész et al. (), we found that speakers’ ratings of the cognitive load increased significantly from the simple task ( M = 5.08, SD = 2.20) to the complex task ( M = 5.87, SD = 1.98), F (1, 38) = 5.56, p = .024, ƞ p 2 = .13. The same was found for writers, whose ratings increased from the simple ( M = 3.64, SD = 1.58) to the complex condition ( M = 5.03, SD = 1.86), F (1, 38) = 19.04, p < .0001, ƞ p 2 = .33.…”
Section: Methodssupporting
confidence: 85%
“…In order to obtain an independent measure of the cognitive load imposed by the task, we employed the Affective Questionnaire (Robinson, 2001), which asks participants to self-assess the mental effort experienced during task performance on a 9-point Likert scale. As in Révész et al (2016), we found that speakers' ratings of the cognitive load increased significantly from the simple task (M = 5.08, SD = 2.20) to the complex task (M = 5.87, SD = 1.98), F(1, 38) = 5.56, p = .024, ƞ p 2 = .13. The same was found for writers, whose ratings increased from the simple (M = 3.64, SD = 1.58) to the complex condition (M = 5.03, SD = 1.86), F(1, 38) = 19.04, p < .0001, ƞ p 2 = .33.…”
Section: The Experimental Tasksupporting
confidence: 73%
See 2 more Smart Citations
“…While no tasks. Speakers' perception of the TOEFL task as the most difficult aligned with our view that it would be the most cognitively challenging, similar to the findings in Révész, Michel, and Gilabert (2015), who studied learner versus expert judgments of task complexity. Thus, the three tasks likely represented different task demands, with the picture and IELTS tasks being less demanding than the TOEFL task.…”
Section: Tablesupporting
confidence: 83%